Geographical distribution of fluoride in the public water supply in the province of Tucumán, Argentina - Raul Alberto Durán; Estela Liliana Durán; Graciela de Jesús Ojeda; Walter Alfredo Castellanos (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2017)
This work studied the geographical distribution of fluoride content in the public water supply in the province of Tucumán, Argentina. A total of 1,210 samples were collected in 190 localities of the 17 departments of the province during the 2008-2012 period. The analytical determination was performed using the SPADNS method and QGis 2.16 was used for processing the information. The fluoride content requirements in the studied localities were determined according to the Argentine Food Code. The results showed that 94% of population studied consumed water with fluoride concentrations below the recommended limits, 5% were exposed to fluoride concentrations above the required maximum limit and 1% consumed water at optimal fluoride concentrations. The maps showed a heterogeneous geographical distribution of fluorides, in which areas with deficit, excess and recommended values of fluorides can be differentiated; in some departments an inverse relationship between the density of the hydrological network and fluoride concentration can be observed. In the capital of the province, the average value found was 0.32 mg/l, presenting a homogeneous geographical distribution. The information obtained is indispensable for the proper management of fluoride, so as to improve public health through policy.